Modelo de Fundraising Mercadológico para la Fundación con Cristo como medio generador de recursos para la sustentación de sus operaciones - Rojas Villagrán, Diana Lucia (2015)
The Fundación Con Cristo was created in 1992 as an initiative of Father Ramiro Rodríguez who, after seeing the precarious life conditions of handicapped children from the South of Quito, decided to undertake this nonprofit deed in order to provide these children with the medical treatment and physical therapy they require. At first, the Foundation received children with all sorts of physical disabilities; however, it was later decided that the Foundation would specialize only on severe cerebral palsy on children. For this reason, the Foundation set up a team of experts in rehabilitation in order to guarantee the effectiveness of the treatments provided. Meanwhile, Father Ramiro Rodríguez was appointed as parish priest of the Church of Nuestra Señora de Fátima de Andalucía, which is why he asked for the support of the members of the parish to provide resources for the Foundation. In the last few years, the low donation income received by the Church has not been able to cover all the expenses generated by the Foundation, which has caused staff rotation. For this reason, I have created a Fundraising Marketing Plan that features several activities which have been analyzed from collected data and surveys. These activities will both allow the members of the parish to make donations and position the Foundation in their minds in order to collect enough resources to keep the Foundation running.